2018
DOI: 10.1007/s11912-018-0681-2
|View full text |Cite
|
Sign up to set email alerts
|

Exercise Training and Cardiovascular Health in Cancer Patients

Abstract: A wealth of clinical studies have documented the safety and benefits of exercise after and during cancer therapy, and pilot and larger-scale studies are currently ongoing to integrate exercise into the treatment program for cancer patients undergoing active therapy (EXACT pilot, OptiTrain, and TITAN study). More recently, efforts have emerged to commence exercise programs before the start of cancer therapy, so-called pre-habilitation. The concept of increasing the cardiovascular reserve beforehand is intuitive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 102 publications
1
38
0
Order By: Relevance
“…For 2019, almost 2 million new cancer diagnoses and just over 600,000 new cancer deaths are estimated; as cancer incidence continues to increase for most cancers, cancer mortality continues to decrease, leading to millions of cancer survivors each year (29). CVD remains a leading cause of death in cancer survivors (second only to cancer recurrence) (4,20,30,31), and shares some risk factors with various cancers. For example, CVD and breast cancer have several risk factors in common, such as unhealthy Western diet, red or processed meat, physical inactivity or sedentary lifestyle, smoking, early menarche, and hormone replacement therapy (20) ( Figures 1C,D, underlined).…”
Section: Cancer Survivorship and Cardiometabolic Riskmentioning
confidence: 99%
See 2 more Smart Citations
“…For 2019, almost 2 million new cancer diagnoses and just over 600,000 new cancer deaths are estimated; as cancer incidence continues to increase for most cancers, cancer mortality continues to decrease, leading to millions of cancer survivors each year (29). CVD remains a leading cause of death in cancer survivors (second only to cancer recurrence) (4,20,30,31), and shares some risk factors with various cancers. For example, CVD and breast cancer have several risk factors in common, such as unhealthy Western diet, red or processed meat, physical inactivity or sedentary lifestyle, smoking, early menarche, and hormone replacement therapy (20) ( Figures 1C,D, underlined).…”
Section: Cancer Survivorship and Cardiometabolic Riskmentioning
confidence: 99%
“…Incorporation of various methodologies in typical cardiac rehabilitation could also have utility for secondary prevention (76), and possibly also primary prevention, of cardiovascular toxicity from a variety of cancer therapies. Some have suggested a multidimensional system consisting of cardiovascular oncology prehabilitation (30,77,78), habilitation (30,79,80), and rehabilitation (30,78,81), to optimize cardiovascular health before, during, and after cancer therapies, respectively. Prehabilitation focuses on optimizing baseline cardiovascular health and cardiopulmonary fitness prior to initiation of cancer therapies (30,77,78).…”
Section: Cardio-oncology or Cardiovascular Oncology Prehabilitation mentioning
confidence: 99%
See 1 more Smart Citation
“…Even in case of patients with specific disorders (e.g. cancer or diabetes) physical activity may bring beneficial effects such as reducing fatigue, improving physical condition, mood and quality of life, helping with cardiovascular integrity, insulin sensitivity, and others (Beuchat-Mamie et al, 2018;Melmer, et al, 2018;Squires, et al, 2018). Thus these activities may bring psychological and physiological benefits (e.g.…”
Section: Benefits Of Physical Activity For Deaf Childrenmentioning
confidence: 99%
“…Among all, physical exercise, whether aerobic, resisted or combined, is known as a health-trigger stress type. [15][16][17][18] Studies have shown that during these different types of physical exercise, the ANP and BNP levels increase significantly in the plasma. 9,19 However, it is not known how much of these NPs are released during the practice of a physical training session.…”
Section: Introductionmentioning
confidence: 99%